THE IMPACT OF INTERNATIONAL AID AND FOREIGN DIRECT INVESTMENT ON ECONOMIC GROWTH IN UKRAINE - FREYER, Eckhard; LISHCHYNSKY, Ihor; LYZUN, Mariia (Journal of European Economy, 2024)
In wartime, the role of international assistance and foreign direct investment in ensuring Ukraine’s economic sustainability has increased. The study examines foreign direct investment (FDI) and international financial assistance as key factors contributing to economic growth. The structure and dynamics of international aid in Ukraine are reviewed. A regression analysis was conducted to determine the impact of international aid (particularly, international development assistance) and FDI on the gross domestic product of Ukraine. The results of the study show a positive impact of both performance parameters, while their values are significant and significantly higher than zero. However, FDI flows have a greater impact on GDP than international development assistance. This suggests that international aid is important for maintaining stability, while FDI has a more significant long-term impact on Ukraine’s economic development, especially in the context of integration into the global economy and attracting innovation. JEL: F21, F35, F43, F63.